Violência contra a mulher e autonomia financeira: uma avaliação do atendimento do Centro de Referência Francisca Clotilde de Fortaleza/Ceará - Cavalcante, Silvana Maria Pereira (2012)
Violence against women is a form of gender violence. It does not occur at random but as the result of a social and cultural process which favors the masculine and culminates in social inequalities between the genders expressed in a condition of submission, subordination and dependence of women on men, including financial dependence. Therefore, financial autonomy represents an important challenge for women regularly subject to gender violence. The objective of this study was to evaluate the service provided by a referral center in Fortaleza (Centro de Referência Francisca Clotilde) for victims of domestic or sexual violence, with emphasis on the development of financial autonomy. Using the hermeneutic-dialectic method and a qualitative approach, the process was evaluated in depth. Information on the service collected through a review of documents was submitted to simple statistical analysis, while information obtained through field interviews with professionals and attendees was submitted to hermeneutic interpretation. The data were used to draw a profile of the attendees and carry out an analysis of the contents expressed in the interviews. The central question of the study was to determine to what extent attending the referral center helps women develop financial autonomy. Many of the attendees were unable to complete the referrals made by the center but adopted alternative strategies to secure a source of income, suggesting the need for reviewing public policies designed to help women in their private and professional life through the development of financial autonomy. The attendees reported experiencing life changes, not as a direct result of the referrals made by the center, but indirectly through interventions favoring the building of autonomy in a wider sense and, consequently, contributing to mitigating gender violence.